2001
DOI: 10.1097/00005537-200110000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Intralaryngeal Ultrasonography

Abstract: Laryngeal lesions can be diagnosed by intralaryngeal ultrasonography using the filling method. Although it does not replace the combination of conventional endoscopy and a critical evaluation of the clinical symptoms of the individual disease, it can profitably complement them. Intralaryngeal ultrasonography can help in determining the extent of tumor involvement during microscopic laser surgery performed under general anesthesia. Confirmation of the results of this pilot study with a larger series of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The boundaries of the tumor could be identified, and radical treatment could be conducted with the minimum necessary resection. 20 In the future, when endoscopic laser surgery is performed for early glottic carcinoma, the role of the voice as the means of communication should be kept in mind during evaluation of the effects arising from treatment of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The boundaries of the tumor could be identified, and radical treatment could be conducted with the minimum necessary resection. 20 In the future, when endoscopic laser surgery is performed for early glottic carcinoma, the role of the voice as the means of communication should be kept in mind during evaluation of the effects arising from treatment of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Arens and Glanz 11 also demonstrated that high-frequency ultrasound allowed clinicians to evaluate the size and infiltration of laryngeal lesions and perform a more accurate preoperative staging than when using CT or MRI. Moreover, Tamura et al 12 characterized the properties of VF nodules, polyps, cysts, and cancer using 30 MHz endolarynx sonography. Tamura et al 13 reported that the epithelium, LP, and VM of the VFs could be visualized by 30 MHz endolarynx sonography.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Although similar results have been demonstrated for the larynx in the past, endosonography has drawn little attention from otolaryngologists thus far. 3,8 However, in a series of 74 patients undergoing surgery for laryngeal cancer at our institution, endolaryngeal ultrasound was shown to have comparable results to CT and MRI, and significantly lower costs, with the advantages of earlier detection of smaller tumours as well as better demonstration of the exact extension, midline crossing and cartilage infiltration of laryngeal lesions. Therefore, this simple and non-invasive method also qualifies for use in the larynx.…”
Section: Discussionmentioning
confidence: 92%